SAT0170 Bdmards Mono vs Combo Therapy in Rheumatoid Arthritis. Analysis of A Rheumatological Single Tertiary Center Real-Life Experience. (15th July 2016) - Farina, I.; Galuppi, E.; Abdel Hafith, B.; Lo Monaco, A.; Govoni, M.
Abstract : Background: Despite adavantages of biological combo therapy over biological mono for RA treatement and the limited approval of biologics as monotherapy (etanercept, adalimumab, certolizumab, tocilizumab), real life registries data revealed that approximately one-third of patients taking biologic agents are using them as monotherapy. Objectives: To assess the prevalence of bDMARDs use as monotherapy (bDMARDs-mono) in a cohort of RA patients treated with bDMARDs attending a tertiary rheumatological center.To characterize the clinical profile of these patients, and to investigate factors related to monotherapy. Methods: All patients with Rheumatoid Arthritis attending our center and receiving bDMARDs up to 31th january 2015 were retrospectively analyzed. Demographic, and clinical characteristics of each patient were recorded: age, gender, disease duration, drugs history and clinical disease activity (DAS28) at last visit. Results: 341 RA patients receiving bDMARDS were included. F 160, M 123, mean age 59.98 ±12.54, disease duration 178.69±101.81 months. 197 patients were taking bDMARD as first line bio-therapy, 144 had been previously treated with one or more bDMARDs. 52% (n=179) of patients were receving bDMARD-mono with a mean disease duration 187.4±125.1 month; 48% (n=162) were bDMARDs-combo, 65% of them with MTX; mean disease duration 168.9±42.4 m. Biologic agents used as mono or combo are shown in table 1 . 32% of bDMARDs-mono had discontinued csDMARDs before starting biological therapy, 68% after an average 50, 4 months after starting bDMARDs (p<0.001). The most common reasons for discontinuing csDMARDs were toxicity (55% of cases), with significant difference between those who stopped before and after starting bDMARDs (66% vs 48% respectively, p<0, 02). 11% of patients discontinue csDMARDs because of nonspecific bad tolerance, 9% for inefficacy, 11% for others unspecified reasons. 25 patients (14%) on bDMARDs-mono stopped csDMARDs for clinical remission. Overall, 57% of RA patients were in clinical remission (DAS28 PCR <2.6) at the time of the inclusion in the study, without significant differece between the two groups (bDMARDs-mono vs combo). The use of bDMARDs-mono was more frequently observed in those patients with disease duration longer than 10 years (p<0, 0001). Conclusions: Biologic monotherapy for managing RA is widely used in our clinical practice especially in patients with long term disease. The proportion of patients (1/3) who start bDMARD-mono is quite similar to that reported in literature. On the other hand, most of patients arrive to bDMARDs-mono after starting biologic agent as the result of csDMARD witdrawal due to AE or intollerance to DMARDs and to a lesser extent because achieving good control of the disease since patient's preference is strongly oriented to csDMARD discontinuation rather than bDMARDs withdrawal or tapering. References: Emery P, et al. Ann Rheum Dis 2013:Dec:72 (12):1897–904. Disclosure of Interest: None declared